'They are stealing my island': Residents' opinions on foreign investment in the residential tourism industry in Tamarin, Mauritius. Issue 2 (May 2016) - Wortman, Tessa; Donaldson, Ronnie; van Westen, Guus
Abstract : The small nation of Mauritius in the Indian Ocean, once a poor sugar plantation island, has successfully diversified and expanded its economy since independence, by attracting foreign investment in manufacturing and modern service industries. Tourism is a major part of the 'Mauritian Miracle'; in recent years residential tourism—attracting wealthy foreigners to take up semi‐permanent residence—has become a growth industry transforming coastal areas like Tamarin. Based on in‐depth interviews among 17 residents of Tamarin, this paper looks at how local people perceive the changes residential tourism is causing in the local area. It appears that while the majority is positive about economic changes like more jobs and income opportunities, and to some extent about improvements in infrastructure and services, there are growing misgivings about some of the social impacts. Notably, the increasing scarcity of land and rising house prices are making it impossible for growing numbers of local people to afford a place to live, resulting in growing squatter settlements in the area. Such growing social disparities challenge the Mauritian development model and may undermine its stability. These undesirable effects call for careful management of tourism development, incorporation of sustainability standards and attention to the position of major stakeholder groups, such as local residents.